Entorno pedagógico para la enseñanza en básica primaria mediante el uso de sistema robótico comercial - Ortega Díaz, Glen Camilo; Téllez Rodríguez, Andrés Felipe; Guarnizo Marin, Jose Guillermo; Camacho Poveda, Edgar Camilo (Ingeniería, 2020)
Context: In this paper, the design of a robotic system applied to learning in primary school is presented. This system is controlled through a mobile application, where two teams competing against each other answer questions about a subject. The robot moves along a racetrack whenever a team answers correctly. The system is designed for easy operation without advanced knowledge in robotics or informatics. Method: First, the results from Colombia’s Pisa tests were consulted, finding that primary school shows a significant weakness in mathematics. Afterwards, a robotic educational platform was designed using a LEGO MINDSTORM robot and a mobile phone app. The education environment was validated by means of perception surveys at the end of an academic activity with 40 students between third and fifth grade. Results: The surveys reported an overall interest and satisfaction from the students with the academic activity and the proposed system. The children were very disciplined in the class with the robot. The activity was supported by the mathematics teacher, who believes that the class yielded positive results, thus contributing to the students’ academic development. Conclusions: The use of robotic platforms contributes to the learning process of children. This is because these activities are appealing and interactive. These kinds of systems are designed to develop teamwork. One important characteristic of these environments must be easy usage since they are conducted by teachers without knowledge in robotics or informatics. These platforms must be more accessible and low-cost, but their design must still be attractive. Acknowledgements: This work was funded by “Decimocuarta convocatoria interna para el formento de la investigación y la innovación FODEIN 2020” at Universidad Santo Tomás, Bogotá, Colombia, entlited “Optimización de trayectorias mediante algoritmos bio-inspirados aplicado a robots móviles con percepción local” (project code 2036004).